Biochemical evaluations of Zingiberaceae sp. and transcriptomics profiling of UV-irradiated normal human adult dermal fibroblast cells for anti-aging - Adekoya, Alafiatayo Akinola (2017)
Skin aging is the gradual building up of molecular damages as a result of production of reactive oxygen species (ROS) due to the vulnerability of the skin to external damaging factors such as solar ultraviolet (UV) radiation. The desire to look youthful is increasingly growing among men and women in today’s world and this has resulted to people willing to spend fortune on anti-aging cosmetic products. However, one major set-back in fighting premature skin aging is that, the numerous anti-aging products currently flooding the markets lack proven efficacy and they have also been reported to be toxic to the human skin. Hence, there is a need to develop an anti-aging cosmetics product from a natural product source with scientifically proven efficacy without any negative side effects. Therapeutic approach to the management of skin aging is to induce the proliferation of dermal fibroblast cells for the production of procollagen and subsequent inhibition of extracellular degrading enzymes (ECM). Plants are source of precursors of many natural products and secondary metabolites with pharmacological and therapeutic potentials. Zingiberaceae family is plants species endowed with great antioxidative properties and are widely distributed in the tropics especially Southeast Asia. The main objective of this study is to evaluate 10 selected indigenous Zingiberaceae plants for their anti-wrinkle potentials via the proliferation of UV irradiated normal human adult fibroblast cells. The selected Zingiberaceae rhizomes were screened by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and ferric reducing antioxidant potential (FRAP) methods for total antioxidant capacity and with high performance liquid chromatography (HPLC) for flavonoid identification and quantification. Biochemical profile was investigated with total protein, lipid, total hydrolysable and reducing sugar, beta carotene and ascorbic acids assays. The profiling of fatty acid was performed using GC-FID fatty acids methyl esters method. Based on the preliminary screening, C. xanthorrhiza and C. longa showed the most potent extracts and were selected for further evaluation. The proliferating capacity of extract on normal human adult dermal fibroblast cells was determined using 3(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide (MTT) assay and anti-wrinkle potentials was assessed by the ability of extracts to inhibit the degrading enzymes, while in vivo toxicity assessment was evaluated with embryos and larval of Zebrafish. Detail molecular profiling was carried out using RNA sequencing technology for the determination of differential expressed genes (DEG). Results obtained from bioinformatics analysis were subjected to Real-Time qPCR. The results revealed high antioxidant capacity in methanol extract of C. xanthorrhiza and C. longa of 245.40±0.5 mg TE/g FW and 270.40±1.6 mg TE/g FW, respectively and were significant at (p<0.05) than other solvents. Although there were variations in different biochemical compounds, C. xanthorrhiza was found to be the topmost of all with 0.52 mg/g FW, 0.1 mg/g FW, 716.73 μg β-carotene/mg FW, 8.7% and 67.05 μg ascorbic/mg FW, respectively. GC-FID fatty acid methyl ester profile revealed the presence of both saturated and unsaturated in most of the samples while C. xanthorrhiza was found to contain more linoleic fatty acid in its oil hence conferred as an excellent candidate for anti-aging cream formulation. C. xanthorrhiza was found to be the best inhibitor of collagenase and hyaluronidase activity with 71.33% and49.78%, respectively while Z. zerumbet displayed the highest elastase inhibition with 87.24% inhibition. Furthermore, extracts from both C. longa and C. xanthorrhiza promoted the proliferations of UV irradiated fibroblast cells at post extract treatment with percentage cell proliferation of 117.4% and 136.1%, respectively, relative to the control. The toxicity assessment of both extracts were found to be embryotoxic with similar teratogenic effects on the Zebrafish embryos and larvae at concentration above 62.5 μg/mL exposed for five days. Based on the therapeutic index (TI) calculated for five days (1.02, 1.00, 1.01, 1.12 and 1.14). C. xanthorrhiza extract was discovered less toxic, therefore was selected for molecular study. The RNA-Sequencing produced about 80 million reads in both UV irradiated and UV irradiated treated samples and 2007 genes were found to be up-regulated and 2791 genes down regulated in UV irradiated human dermal fibroblast (HDF) cells (Sample U1). In the same manner, extract of C. xanthorrhiza treated UV- irradiated HDF cells (Sample T2) yielded 2284 up-regulated genes and 2968 down regulated genes while the comparison of the two results generated 19 genes up regulated and 19 genes down regulated these set of genes were the target genes in this study. About 19000 transcripts were reported as novel and gene ontology (GO) functional annotations have categorized the genes into various functions. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analysis implicated cancer and cytokine-cytokine receptor interaction in UV-irradiated HDF cells leading to induction of cells apoptosis as reported in the cell proliferation results in this study. The Real-Time qPCR gene expression profiling confirmed the expression of eight significantly differential expressed genes that were selected from the list of target genes to be in the same trend as obtained in the RNASeq analysis. HIST1H2AG, ELOVL3, OSR2 and TNFSF10 were up-regulated in sample U1 but down regulated in sample T2 while FAM111B, IVL, MFSD2A and CCNE2 were down-regulated in sample U1 but Up-regulated in sample T2. Thus, these set of confirmed genes were concluded to be potential candidates’ for biomarkers development for diagnostic, personalize and precise treatment of UV-induced premature aging. Therefore, C. xanthorrhiza could be potential lead to address the problems and issues of toxicity and efficacy associated with most available anti-aging cream.